Construção, validação de conteúdo e aplicação do protocolo avaliativo de iniciação esportiva em cadeira de rodas - Melo, Flávio Anderson Pedrosa de (Universidade Federal de São Carlos, 2018)
The evaluation is part of any teaching and learning process. It allows the educator to follow the evolution of the respective learner, establishing parameters that allow to identify the areas in which the same needs more stimulation. In view of the difficulty of finding tools for the evaluation of motor components for sports initiation for people and children with physical disabilities. This study presents an evaluation protocol based on the compilation, adaptation and creation of tests involving motor components present in the sports initiation process represented by the fundamentals and behaviors of sports modalities in wheelchairs. The aim of this study was to develop and validate the Wheelchair Sportive Initiation Protocol (WSIP). This protocol aim to evaluating the motor components that influence the wheelchair sports initiation process. And more specifically to contextualize the process of elaboration and construction of the WSIP; To analyze the contents of the WSIP according to the perspective of expert judges (content validation); To verify the adequacy and applicability of the WSIP. The study involving a qualitative and quantitative research approach. It is characterized by descriptive and cross-sectional study. The research was divided in three studies: I) Development of the WSIP; II) Content Validation; III) Application Study. The second study participants were specialist teachers in Adapted Physical Education or Special Education. The third study participants were children of both sexes with physical disabilities. For this study the age was between 6 and 13 years. The data analysis was used the statistical descriptive analysis. After the study it was possible to develop and content validate the WSIP as well as identify potential weaknesses and problems through the applications as a way to solve them. The intention was allows the educator to follow the evolution of the student establishing parameters that make it possible to identify the areas in which needs more stimulation for influencing behaviors of wheelchair sports initiation.
Construction, content validation and application of the wheelchair sportive initiation protocol
Construcción, validación de contenido y aplicación del protocolo evalutivo de iniciación deportiva en la silla de ruedas
Keywords: Educação especial; Educação física adaptada; Avaliação; Iniciação esportiva; Deficiência física; Special education; Adapted physical education; Evaluation; Sports initiation; Physical impairment; CIENCIAS HUMANAS::EDUCACAO